Carbon nanodots prepared for cellular imaging and turn-on detection of glutathione. Issue 23 (31st May 2016) - Kong, Depeng; Yan, Fanyong; Luo, Yunmei; Wang, Yinyin; Chen, Li; Cui, Fenghai
Abstract : Carbon nanodots as fluorescent probes were synthesized through a one-step hydrothermal method. The carbon nanodots can be used not only for multicolor intracellular imaging but also for highly sensitive and selective turn-on detection of glutathione. Abstract : A simple one-step hydrothermal method was designed to synthesize fluorescent carbon nanodots (CNDs). The resulting CNDs exhibited excellent properties such as good solubility, superior photo-stability and low toxicity. Significantly, the CNDs were found to be an effective fluorescence sensing platform for turn-on detection of glutathione (GSH). The initial fluorescence of CNDs was quenched through an electron transfer process in the presence of dopamine, while the quenched fluorescence was enhanced with the further addition of GSH. Moreover, it showed a good linear relationship between GSH concentration and the relative fluorescence intensity of the system. Significantly, this sensing platform successfully detected GSH in biological fluids, indicating its potential applications in the field of biology.